The Rule of One-Third - Rick Geddes; Paul J. Zak (Claremont McKenna College, Department of Economics, 2000)
The Rule of One-Third guaranteed wives one-third of their husband's estate upon marital dissolution through death or divorce. We document the historical ubiquity of this legal construct and show that without a wife's residual claim on her husband's estate, children's outcomes are imperiled. Using ancient Roman law as an example, we argue that the patriarch, or paterfamilias is the main legal entity with an interest in creating and enforcing the Rule of One-Third. Then, in a game-theoretic model, we demonstrate that the Rule of One-Third obtains when mothers' and fathers' marginal impacts on their children's human capital are equal. We conclude that the Rule of One-Third arose in many societies because it places the cost of marital dissolution on the household rather than society and solves a complex contracting problem between the husband and wife when each is specialized in tasks the other cannot perform well.
Keywords: J12; K00; 330; marriage; divorce; human capital; institutions